Changing Migration Landscape in Latin America in 21st Century - O. N. Bogatyreva; E. D. Krapivnitskaya (Научный диалог)
This article explores the key components and routes of migration flows in Latin America and the Caribbean (LAC) from the late 20th to the early 21st century. Special attention is given to the specificities of migration processes within the subregions of LAC—South America, Central America, and the Caribbean. The management of migration processes in the region is also addressed. It has been established that new mobility patterns have led to changes in regional and national migration policies. The interaction among LAC countries within regional integration organizations — such as the Common Market of the South, the Andean Community, and the South American Conference on Migration — is highlighted, emphasizing the development of subregional migration regimes that balance state control with human rights compliance. The findings indicate that states have deviated from a coordinated regional consensus on the “right to migrate,” shifting significantly toward securitization and externalization in light of their internal and external political interests. National strategies and tools for managing migration are identified, along with the influence of both external and internal factors on the formulation of migration policy.